Professional development for English-medium instruction professors at Korean universities - Park, Seonmin; Kim, Sung-Yeon; Lee, Hikyoung; Kim, Eun Gyong (System (Linköping), 2022)
English-medium instruction (EMI) has been implemented in higher education institutions mainly to foster internationalization. This study examines EMI-related professional development (PD) programs, professors' experiences and perceptions of such programs, and EMI certification implementation at comprehensive universities and science and engineering universities in South Korea. A mixed-methods analysis was conducted to investigate the current state of EMI and the need for EMI-related PD programs at the universities. Furthermore, a survey was administered to professors to examine their perceptions of EMI, EMI-related PD programs, and EMI certification implementation. Follow-up interviews were also conducted for a more in-depth analysis. The analysis results show that the EMI implementation rate was higher in science and engineering universities than in comprehensive universities, whereas more systematic and substantive EMI-related PD programs were offered at comprehensive universities. Survey findings indicated that few professors had experience with pre- or in-service PD programs, and that professors showed negative tendencies towards EMI certification implementation. Moreover, professors’ attitudes towards the benefits, challenges and importance of EMI differed among the university types sampled. This study proposes an EMI PD model and highlights the need for a context-appropriate approach to EMI-related PDs to meet not only institutional but also faculty needs regarding EMI policy.